Physical and chemical characteristics of enzymatically modified Batu banana (Musa balbisiana Colla) and Kepok banana (Musa paradisiaca formatypica) flours - Anjani, G. (2024)
Batu (Musa balbisiana Colla) and Kepok (Musa paradisiaca formatypica) bananas are two food commodities with high resistant starch content. The later has been suggested to prevent colorectal cancer. Modifications of these, into flour via the addition of pullulanase enzymes and autoclaving-cooling method are expected to improve the quality. The physical characteristics, levels of resistant starch, amylose, amylopectin and in vitro digestibility of enzymatically modified banana starches were determined. Therefore, a descriptive study was performed with untreated Batu banana flour (TP), autoclavingcooling (AC), autoclaving-cooling + pullulanase enzyme (AC + E), and autoclavingcooling + pullulanase enzyme + autoclaving-cooling (AC + E + AC). The granular morphology, water absorption, and swelling ability were evaluated as physical characteristics. Amylose, amylopectin content, and starch digestibility were evaluated as chemical characteristics. Based on SEM, the analysis of granular morphology showed structural modification in both treatments, although Batu banana flour showed greater water absorption and swelling ability, with and without AC + E + AC. However, both samples demonstrated better outcomes, in terms of high levels of starch resistance, low amylose, high amylopectin, and low in vitro digestibility after treatment with AC + E + AC.